Existence of Periodic Solutions for a Class of Difference Systems with p-Laplacian. (12th July 2012) - Chen, Kai; Zhang, Qiongfen
Abstract : By applying the least action principle and minimax methods in critical point theory, we prove the existence of periodic solutions for a class of difference systems with p -Laplacian and obtain some existence theorems.